ON THE PERFORMANCE OF OTTER TRAWLS OPERATED FROM A 15.4 M TRAWLER OFFVERAVAL - VIJAYAN, V; RAMA RAO, S V. S (Fishery Technology, 2017)
Results obtained with three trawl nets namely, 13.7 m four seam, 15.8 m six seamand 18.3 m four seam operated from a 15.4 m wooden trawler, are presented.Among the three nets operated, 15.8 m six seam trawl and 18.3 four seam trawl were found to be equally effective for the capture of shrimp and during the lean season 15.8 m six seam trawl can be successfully operated to exploit demersal as well as semipelagic fish resources. The catch data were analysed using analysis of variance and Gulland's method.